2019
DOI: 10.1021/acs.organomet.9b00377
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tungsten Oxo Alkylidene Biphenolate Complexes and Ring-Opening Metathesis Polymerization of Norbornenes and Norbornadienes

Abstract: We have synthesized and characterized tungsten oxo alkylidene biphenolate complexes with the formulas W(O)(CHR)(rac-biphenolate)-(PPhMe 2 ) and (R,S)-[W(μ-O)(CHR)(biphenolate)] 2 (R = CMe 2 Ph; biphenolate = L1 or L2 in the text). They behave as initiators for the stereoselective (cis,isotactic) polymerization of 2,3-dicarbomethoxy-5-norbornadiene and eight enantiomerically pure 5-substituted norbornenes with a cis,isotactic precision of 95−98% in most cases. The active initiators are 14e W(O)(CHR)(biphenolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
(34 reference statements)
2
9
0
Order By: Relevance
“…In the subsequent years, the Schrock group reported other tungsten oxo alkylidenes and the role of ancillary ligands on the catalytic activity and product selectivity were deeply discussed (i.e. 15 and 16) [36][37][38][39][40][41][42]. Moreover, Buchmeiser and co-workers synthetized a series of very active cationic tungsten oxo alkoxy alkylidene bearing an N-heterocyclic carbene (NHC) as fourth ligand (17)(18) [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…In the subsequent years, the Schrock group reported other tungsten oxo alkylidenes and the role of ancillary ligands on the catalytic activity and product selectivity were deeply discussed (i.e. 15 and 16) [36][37][38][39][40][41][42]. Moreover, Buchmeiser and co-workers synthetized a series of very active cationic tungsten oxo alkoxy alkylidene bearing an N-heterocyclic carbene (NHC) as fourth ligand (17)(18) [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies of the polymerization of DCMNBD by 4 W (2% in CDCl 3 ) showed that polymerization is complete in 10 min to give >99% cis , syndiotactic -poly­(DCMNBD), a result that is characteristic of certain other imido MAP initiators and analogous to the selective polymerization of DCMNBD by ( R , S )-[W­(μ-O)­(CHCMe 2 Ph)­(biphenolate)] 2 to afford the cis isotactic polymer as a consequence of dissociation of the dimer into monomers . DCMNBD is also immediately polymerized by 2 W , but the resulting polymer is approximately a 1:1 mixture of cis and trans structures, consistent with facile cleavage of the dimer into 14-electron monomers, but those are not cis-selective initiators, as expected.…”
mentioning
confidence: 96%
“…The adamantylidene ligand is slightly disordered in the structural study, but the WC bond length (1.896(2) Å) could be determined accurately. The structure of 2 W is similar to that of ( R , S )-[W­(μ-O)­(CHCMe 2 Ph)­(biphenolate)] 2 , which initiates polymerization of 5,6-dicarbomethoxynorbornadiene (DCMNBD) to form the cis isotactic polymer selectively through facile dissociation of the dimer to a small degree into 14-electron monomeric units …”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The few reports that do exist are almost exclusively focused on aza Diels-Alder reactions. [40][41][42][43][44][45][46] However, the utilization of nitroso Diels-Alder adducts as monomers for ROMP could allow for the preparation of some interesting, polar functional group-containing "polyolefins," materials of high interest to the polymer science community (Figure 1d). [47] This is especially interesting as it could possibly lead to polymers containing primary amines, materials that are challenging to prepare with ROMP.…”
Section: Introductionmentioning
confidence: 99%